Answer:
![\large \boxed{\sf \bf \ \ f(x)=(x-4i)(x+4i)(x+3)(x-5) \ \ }](https://img.qammunity.org/2021/formulas/mathematics/college/676njyg55izu5fuaqxchiwrxe2qm13spht.png)
Explanation:
Hello, the Conjugate Roots Theorem states that if a complex number is a zero of real polynomial its conjugate is a zero too. It means that (x-4i)(x+4i) are factors of f(x).
![\text{Meaning that } (x-4i)(x+4i) =x^2-(4i)^2=x^2+16 \text{ is a factor of f(x).}](https://img.qammunity.org/2021/formulas/mathematics/college/xjysjkng1359c6yckn8dv37nuagr317r78.png)
The coefficient of the leading term is 1 and the constant term is -240 = 16 * (-15), so we a re looking for a real number such that.
![f(x)=x^4-2x^3+x^2-32x-240\\\\ =(x^2+16)(x^2+ax-15)\\\\ =x^4+ax^3-15x^2+16x^2+16ax-240](https://img.qammunity.org/2021/formulas/mathematics/college/7osl0k9hmhv3olhagivr5to7szcidgdw1e.png)
We identify the coefficients for the like terms, it comes
a = -2 and 16a = -32 (which is equivalent). So, we can write in
.
![\\f(x)=(x^2+16)(x^2-2x-15)](https://img.qammunity.org/2021/formulas/mathematics/college/eh041fxqm16gixuh94atpnx00m1ux780uj.png)
The sum of the zeroes is 2=5-3 and their product is -15=-3*5, so we can factorise by (x-5)(x+3), which gives.
![f(x)=(x^2+16)(x^2-2x-15)\\\\=(x^2+16)(x^2+3x-5x-15)\\\\=(x^2+16)(x(x+3)-5(x+3))\\\\=\boxed{(x^2+16)(x+3)(x-5)}](https://img.qammunity.org/2021/formulas/mathematics/college/1uap84mtvvfkiut2xjw2oaquvwwhwr60xt.png)
And we can write in
![\mathbb{C}](https://img.qammunity.org/2021/formulas/mathematics/high-school/cdcf1op63wmkutr0hor18awuodvpekndwm.png)
![f(x)=\boxed{(x-4i)(x+4i)(x+3)(x-5)}](https://img.qammunity.org/2021/formulas/mathematics/college/pnh7fxy90e6ldx5z6jo8vo4biqb4a1qvlo.png)
Hope this helps.
Do not hesitate if you need further explanation.
Thank you